Pengaruh Perlakuan Media Tumbuh terhadap Perkecambahan Benih Kayu Merah (Pterocarpus Indicus Willd) - Jeriels Matatula; Flora Evalina Ina Kleruk (Politeknik Pertanian Negeri Kupang, 2013)
Pterocarpus indicus Willd (Kayu Merah) is a straight bole hardwood plant that is easily grown in tropical areas such as Indonesia. In the East Nusa Tenggara Province, this plant is becoming rare which results in an effort of development and conservation of the species by the government through plant propagation. One of the ways of conserving the plant is through plant propagation. Problems faced in the propagation method through nurseries are breaking the dormant periode of kayu merah and finding the right media. The aim of this research is to understand the influence of treatment of growth medium in the kayu merah’s germination. This research used completely randomized design with various treatments such as sand, black soil, bokasi, soil : sand (3:1), soil;sand;bokasi (3:2:2), soil:sand (1:1), soil:sand:bokasi (1:1:1) and soil:fertiliser (1:1). Every treatment was redone three times. The analysis used was analysis of varians followed by Significant difference test. The results showed that the highest successful of germination was the treatment using sand as the medium because of the good drainage so that the moisture level was optimum. On the other hand, the lowest was the treatment using bokasi as the medium because of the high moisture level which resulted in the decay of the seeds of kayu merah. Key words: growth media, germination, kayu merah